Dietary advanced glycation products and their associations with insulin sensitivity and body weight: A 16‐week randomized clinical trial - Hana Kahleova; Tatiana Znayenko‐Miller; Jaime Uribarri; Richard Holubkov; Neal D. Barnard (Wiley, 2023)
Abstract Background Evidence suggests that changes in advanced glycation end‐products (AGEs) may influence body weight. Previous studies have focused on cooking methods as the primary way how to reduce the dietary AGEs but little is known about the effects of a change in diet composition. Objective The aim of this study was to assess the effects of a low‐fat plant‐based diet on dietary AGEs and test the association with body weight, body composition, and insulin sensitivity. Methods Participants who were overweight (n = 244) were randomly assigned to an intervention (low‐fat plant‐based) (n = 122) or control group (n = 122) for 16 weeks. Before and after the intervention period, body composition was measured by dual X‐ray absorptiometry. Insulin sensitivity was assessed with the predicted insulin sensitivity index (PREDIM). Three‐day diet records were analyzed using the Nutrition Data System for Research software and dietary AGEs were estimated, using a database. Repeated measure ANOVA was used for statistical analysis. Results Dietary AGEs decreased in the intervention group by 8768 ku/day on average (95% −9611 to −7925; p < 0.001), compared with the control group (−1608; 95% CI −2709 to −506; p = 0.005; treatment effect −7161 ku/day [95% CI −8540 to −5781]; Gxt, p < 0.001). Body weight decreased by 6.4 kg in the intervention group, compared with 0.5 kg in the control group (treatment effect −5.9 kg [95% CI −6.8 to −5.0]; Gxt, p < 0.001), largely due to a reduction in fat mass, notably visceral fat. PREDIM increased in the intervention group (treatment effect +0.9 [95% CI + 0.5 to +1.2]; p < 0.001). Changes in dietary AGEs correlated with changes in body weight (r = +0.41; p < 0.001), fat mass (r = +0.38; p < 0.001), visceral fat (r = +0.23; p < 0.001), and PREDIM (r = −0.28; p < 0.001), and remained significant even after adjustment for changes in energy intake (r = +0.35; p < 0.001 for body weight; r = +0.34; p < 0.001 for fat mass; r = +0.15; p = 0.03 for visceral fat; and r = −0.24; p < 0.001 for PREDIM). Conclusions Dietary AGEs decreased on a low‐fat plant‐based diet, and this decrease was associated with changes in body weight, body composition, and insulin sensitivity, independent of energy intake. These findings demonstrate positive effects of qualitative dietary changes on dietary AGEs and cardiometabolic outcomes. Clinical Trial Registry Number NCT02939638.